The effect of T. aestivum chromosomes 1A and 1D on fertility of alloplasmic recombinant (H. vulgare)-T. aestivum lines depending on cytonuclear compatibility - L. A. Pershina; N. V. Trubacheeva; V. K. Shumny (Вавиловский журнал генетики и селекции, 2024)
The effect of T. aestivum L. chromosomes 1A and 1D on fertility of recombinant bread wheat allolines of the same origin carrying the cytoplasm of barley H. vulgare L. and different levels of cytonuclear compatibility was studied. Alloline L-56 included mainly fully sterile (FS) and partially sterile (PS) plants, alloline L-57 included partially fertile (PF) plants and line L-58 included fertile (F) ones. Analysis of morphobiological traits and pollen painting indicated complete or partial male sterility in plants of allolines L-56 and L-57. To differentiate genotypes with cytonuclear coadaptation and genotypes with cytonuclear incompatibility, PCR analysis of the 18S/5S mitochondrial (mt) repeat was performed. Heteroplasmy (simultaneous presence of barley and wheat mtDNA copies) was found in FS, PS, PF and some F plants, which was associated with a violation of cytonuclear compatibility. Wheattype homoplasmy (hm) was detected in the majority of the fertile plants, which was associated with cytonuclear coadaptation. The allolines used as maternal genotypes were crossed with wheat-rye substitution lines 1R(1A) and 1R(1D). In F1, all plants of PF×1R(1A) and PF×1R(1D) combinations were fertile, and in F2, a segregation close to 3 (fertile) : 1 (sterile) was observed. These results showed for the first time that chromosomes 1A and 1D carry one dominant Rf gene, which controls the restoration of male fertility of bread wheat carrying the cytoplasm of H. vulgare. All plants of F1 combinations FS×1R(1A), FS×1R(1D), PS×1R(1A), PS×1R(1D) were sterile, which indicates that a single dose of genes localized on wheat chromosomes 1A or 1D is not enough to restore male fertility in FS and PS plants. All plants of hybrid combinations F(hm)×1R(1A) and F(hm)×1R(1D) in both F1 and F2 were fertile, that is, fertility of allolines with cytonuclear coadaptation does not depend on wheat chromosomes 1A and 1D.